Elaine Steinbeck with Betty Comden and Adolph Green
Elaine Steinbeck with the legendary duo of Betty Comden and Adolph Green at renaming of Bay Street Theatre's stage after Elaine Steinbeck. Comden and Green performed various skits for the celebration. The Bay Street Theatre is located in Sag Harbor, New York.